Konsep Nasākh wal Mansūkh - Panji Nurrahman (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2024)
The theory of nasakh wal mansukh is still debated until now both among scholars of tafsir and among scholars of usul fiqh. This paper aims to explain the concept of nasakh wal mansukh offered by two contemporary scholars as a form of their response to the on-going debate. The two contemporary scholars are Abdullah Ahmad An-Na'im and Abdullah Saeed. This paper is a form of library research and is a type of qualitative research. The data in this paper is obtained from searching written sources such as books and articles. The data that has been obtained is then presented in descriptive form to provide a clear understanding of the reader of the data collected. The results of this study found that according to Abdullah Ahmad An-Na'im, nasakh is the delay in the enforcement of a shar'i law until the situation and conditions that require it to apply again. Meanwhile, according to Abdullah Saeed, nasakh is the revocation of a Shar'i law with a law that comes after it.